Social implications of knowing Yahweh A study of Jeremiah 9:22–23 - Wessels, Willie 1953- (2009)
In the brief passage of Jeremiah 9:22-23, wisdom, might and riches are explicitly rejected as reasons for boasting. The only true reason for boasting is if a person ‘knows Yahweh’. In verse 23, this is linked with three other concepts: steadfast love, justice and righteousness. Jeremiah described the society of his day as corrupt in every sense of the word. People were stubborn, refused to acknowledge Yahweh and showed no signs of truly knowing him. They had, in fact, deserted the Torah of Yahweh. To know Yahweh has social implications. The rhetorical appeal of Jeremiah 9:22-23 to readers and hearers of this oracle is quite clear. To know Yahweh is not to claim to be wise or be the strongest or have the most possessions but to respond to Yahweh’s way of acting. This implies an understanding of his loving-kindness and acting in a morally correct way.
Keywords: Justice; knowing Yahweh; loving-kindness; Righteousness; Wisdom